Translation in context : selected contributions from the EST Congress, Granada, 1998 - Chesterman, Andrew; Gallardo San Salvador, Natividad; Gambier, Yves, 1949- (Benjamins translation library, 2000)
Translation in Context is a collection of contributions from the 1998 Congress arranged by EST, the European Society for Translation Studies, in Granada, Spain. It illustrates some of the latest research interests and achievements in Translation Studies at the turn of the millennium. The contributions show how the context of Translation Studies has expanded to cover new documentation techniques, cultural and psychological factors, the latest computer tools, ideological issues, media translation, and new methodologies. A total of 32 papers deal with: (I) Conceptual analysis in Translation Studies, (II) Situational, sociological and political factors, (III) Psychological and cognitive aspects, (IV) Translation effects, (V) Computer aids, (VI) Text-type studies, (VII) Culture-bound concepts, and (VIII) Translation history. The languages of the papers and abstracts are English, French, German and Spanish.